2009
DOI: 10.1038/oby.2008.649
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Overweight/Obese Women and Its Relationship With Dietetic and Anthropometric Variables

Abstract: Overweight/obese persons usually have an inadequate vitamin D status, a situation commonly made worse by an inadequate intake of this vitamin. For this reason, the aim of this study was to analyze dietetic and anthropometric differences in a group of young, overweight/obese Spanish women with respect to their vitamin D status. The study subjects were 66 white Spanish women (aged 20-35 years) with a BMI of 24-35 kg/m(2). Dietetic, anthropometric, and biochemical data were collected. Women were divided into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 38 publications
10
48
3
3
Order By: Relevance
“…A number of studies have reported a negative association between serum 25(OH)D concentration and body fat (Alemzadeh et al, 2008;McKinney et al, 2008;Kremer et al, 2009), perhaps due to the sequestration of the vitamin by the fat (Liel et al, 1988). Several studies performed on adults have reported a negative relationship between BMI and serum levels of vitamin D (Need et al, 2005;Konradsen et al, 2008;Kremer et al, 2009;Rodríguez-Rodríguez et al, 2009), and the same has been reported for children and adolescents (Alemzadeh et al, 2008;Bener et al, 2008a, b). In a group of 127 children and adolescents, Alemzadeh et al (2008) observed that those with serum 25(OH)D concentrations of o75 nmol/l had a greater BMI than those with higher concentrations (38.2±8.9 vs 33.9±6.0 kg/m 2 ; Po0.02).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported a negative association between serum 25(OH)D concentration and body fat (Alemzadeh et al, 2008;McKinney et al, 2008;Kremer et al, 2009), perhaps due to the sequestration of the vitamin by the fat (Liel et al, 1988). Several studies performed on adults have reported a negative relationship between BMI and serum levels of vitamin D (Need et al, 2005;Konradsen et al, 2008;Kremer et al, 2009;Rodríguez-Rodríguez et al, 2009), and the same has been reported for children and adolescents (Alemzadeh et al, 2008;Bener et al, 2008a, b). In a group of 127 children and adolescents, Alemzadeh et al (2008) observed that those with serum 25(OH)D concentrations of o75 nmol/l had a greater BMI than those with higher concentrations (38.2±8.9 vs 33.9±6.0 kg/m 2 ; Po0.02).…”
Section: Discussionmentioning
confidence: 99%
“…The median vitamin D intake in our sub-population of 8.4 mg/day was normal according to current Nordic recommendations. A recent Spanish study also reported adequate vitamin D intake according to regional recommendations in overweight and moderately obese women (Rodriguez-Rodriguez et al, 2009). Previous studies have shown that obese subjects tend to underreport EIs (Heitmann and Lissner, 1995;Johansson et al, 1998), especially women (Johansson et al, 1998).…”
Section: Seasonal Variation Vitamin D Intake and Gendermentioning
confidence: 94%
“…However, vitamin D is currently considered a true steroid hormone, and due to its significant influence on metabolism and cell proliferation [6], vitamin D deficiency has been associated with several diseases such as obesity and diabetes [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%